Psoriasis prevalence among the 2009 AAD National Melanoma/Skin Cancer Screening Program participants. (4th April 2012) - Lima, X.T.; Minnillo, R.; Spencer, J.M.; Kimball, A.B.
Abstract Background Validated epidemiological estimates of the prevalence of skin diseases remain an unmet challenge. Most patients in many health care systems do not see dermatologists for skin problems. Assessments based on claims data or self‐report are likely to contain substantial misclassification. Population‐based in‐person dermatological exams have proven impractical because of the number of patients required. However, in the US, there is a large skin cancer screening program where volunteer dermatologists assess almost 100 000 people annually. Objective To evaluate the utility of this program for the assessment of other diseases. Methods Information concerning prior diagnosis of psoriasis, type of insurance and physician's current assessment of psoriasis was captured as part of the American Academy of Dermatology National Melanoma/Skin Cancer Screening Program. A modified form was provided to a subset of participant sites. Overall and subgroup prevalence of psoriasis was analysed. Crude and adjusted results are presented for comparison to the US population. Results Among the 2991 participants, 86% answered the self‐report psoriasis question. A previous diagnosis of psoriasis was reported by 5.1% of them. This proportion was greater than the prevalence of physician documented diagnosis of psoriasis (2.8%). Analyses with different assumptions to account for missing values and weighting based on US population estimates yielded prevalence values ranging from 1.2% to 3.4%. Conclusion This project, although limited by missing data, is consistent with previous findings that psoriasis prevalence is between 2.2% and 4.6% in the US. It demonstrates the potential to evaluate prevalence of other skin conditions through existing national activities.